A systematic review of primary large cell neuroendocrine carcinoma of the prostate - Nguyen, Ngan; Franz, Ronald Dean; Mohammed, Omar; Huynh, Richard; Son, Christine Kim; Khan, Rida Nusrat; Ahmed, Bilawal (Frontiers in Oncology, 2024)
Background: Large cell neuroendocrine carcinoma (LCNEC) is a rare subtype of prostate cancer. The pathogenesis, clinical manifestation, treatment options, and prognosis are uncertain and underreported. Materials and Methods: A systematic search was conducted in April 2022 through PubMed, Embase, and Cochrane. We reviewed cases of LCNEC developed either from de novo or transformation from prostate adenocarcinoma and summarized the relevant pathophysiological course, treatment options, and outcomes. Results: A total of 25 patients with a mean age of 70.4 (range 43 – 87 years old) from 18 studies were included in this review. 13 patients were diagnosed with de novo LCNEC of the prostate. 12 patients were from the transformation of adenocarcinoma post-hormonal therapy treatment. Upon initial diagnosis, patients diagnosed with de novo prostatic LCNEC had a mean serum PSA value of 24.6 ng/ml (range: 0.09-170 ng/ml, median 5.5 ng/ml), while transformation cases were significantly lower at 3.3 ng/ml (range: 0-9.3 ng/ml, median 0.05 ng/ml). The pattern of metastasis closely resembles prostate adenocarcinoma. Six out of twenty-three cases displayed brain metastasis matching the correlation between neuroendocrine tumors and brain metastasis. Three notable paraneoplastic syndromes included Cushing’s syndrome, dermatomyositis, and polycythemia. Most patients with advanced metastatic disease received conventional platinum-based chemotherapy with a mean survival of 5 months. There was one exception in the transformation cohort with a somatic BRCA2 mutation who was treated with a combination of M6620 and platinum-based chemotherapy with an impressive PFS of 20 months. Patients with pure LCNEC phenotype have worse survival outcomes when compared to those with mixed LCNEC and adenocarcinoma phenotypes. It is unclear whether there is a survival benefit to administering ADT in pure pathologies. Conclusion: LCNEC of the prostate is a rare disease that can occur de novo or transformation from prostatic adenocarcinoma. Most patients present at an advanced stage with poor prognosis and are treated with conventional chemotherapy regimens. Patients who had better outcomes were those who were diagnosed at an early stage and received treatment with surgery or radiation and androgen deprivation therapy (ADT). There was one case with an exceptional outcome that included a treatment regimen of M6620 and chemotherapy.